(untitled) (Biological Sciences - PJSIR, 1999)
Phytosociology of weedswasstudiedinboro (winter)riceinhaorareainrelationtoweedingregimeandureatopdressing throughaweedsurvey. 16,18and 13weedspecieswererecordedinthefieldsreceivingthreedifferentregimesofweeding., Scirpus junco ides wasthemostdominantspecies. Awiderangeofdissimilarityinweedinfestationwasobserved inthose fields. The fields receiving 15-20, 8-14 and 0-7 kg ha’ of urea as top dressing recorded 14, 21 and 17 weed species respectively. Scirpus juncoides was alsothemostdominantweedspecies. Awiderangeofdissimilarity andsevere weed infestation was observed in thefields receivingurea as topdress.